Gachiakuta. 1 - Urana, Kei (Kodansha USA Publishing, LLC, 2024)
Rudo lives in the slums of a floating town, where the poor scrape by under the shadow of the rich, who live a sumptuous life, simply casting their garbage off the side, into the abyss. Then one day, he's falsely accused of murder, and his wrongful conviction leads to an unimaginable punishment-exile off the edge, with the rest of the trash. Down on the surface, the cast-off waste of humanity has bred vicious monsters, and if Rudo wants to have any hope of discovering the truth and seeking vengeance, he will have to master a new power and join a group known as the Cleaners who battle the hulking trash beasts of the Pit!